THE MN, MG-INTRACRYSTALLINE EXCHANGE REACTION IN DONPEACORITE (MN0.54CA0.03MG1.43SI2O 6) AND ITS RELATION TO THE FRACTIONATION BEHAVIOR OF MN IN FE, MG-ORTHOPYROXENE - Stimpfl M. (My University, 2005)
The equilibrium intracrystalline distribution of Mn and Mg between the M1 and M2 sites of a Mn-rich/Fe-free orthopyroxene (donpeacorite) was investigated by means of annealing experiments at temperatures between 980 and 800 °C and single-crystal X-ray diffraction. The data show that Mn, as does Fe2+ in Fe-Mg orthopyroxene, preferentially orders at the M2 site. However, comparison of the distribution coefficient kD(Mn-mg) determined in this study with k D* measured for Fe-Mg orthopyroxene shows that Mn has a much stronger preference for the M2 site relative to Fe 2+. This result implies that the practice to partition Fe2+ + Mn = Fe* as one species, typically implemented to determine the quenched-site occupancies in Fe-rich /Mn-poor orthopyroxene, should be abandoned and that Mn should be considered totally ordered at M2. The partitioning method, i.e., Fe vs. Fe*, has implications for the determination of cooling rates from the observed ordering state of orthopyroxene, particularly for Fe-poor compositions (Fs <0.16).